Quantity or quality? Knowledge alliances and their effects on patenting - Hanna Hottenrott; Cindy Lopes-Bento (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
This study shows for a large sample of R&D-active manufacturing firms over the period 2000-2009 that knowledge alliances have a positive effect on patenting in terms of both quantity and quality. However, when distinguishing between alliances that aim at joint creation of new knowledge and alliances that aim at the exchange of knowledge, results suggest that creation alliances lead to more valuable patents as they receive significantly more forward citations per patent. Knowledge exchange alliances, on the other hand, are associated with patent quantity, but not quality.
Keywords: O31; O32; O33; O34; 330; Knowledge Alliances; Patents; Innovation; R&D; Count Data Models